ECONOMIC POTENTIAL OF MAIZE (ZEA MAYS L) FARMING IN KOTA BAHAGIA SUB-DISTRICT, SOUTH ACEH DISTRICT - Qhisthina Atikah; Bagio; Nurlaili; Safrika; Abdul Muzammil (RADJA PUBLIKA, 2024)
The government prioritizes increasing the production of rice and maize as staples and raw materials for the animal feed industry. Maize (Zea Mays L.), the second major source of carbohydrates after rice, continues to increase in use as food and animal feed in Indonesia. Increased maize production is needed through land expansion and increased productivity to meet growing market demand. The research was conducted in Kota Bahagia Subdistrict, South Aceh District, the research began in August to September 2023 with a population of 1,450 farmers, with a sample of 94 corn farmers in Kota Bahagia Subdistrict, South Aceh. The results showed that the average income of maize farmers was IDR 17,758,435.36 per growing season, which is above the local poverty line. Revenue Cost Ratio (R/C Ratio) and Return on Investment (ROI) analysis amounted to 2.36 and 135.60%, respectively, indicating efficient use of capital and significant profits. The Break Even Point (BEP) of production and selling price of 3,274.08 kg per period and IDR 1,697.80 per kg indicate that the farm is profitable.